2017
DOI: 10.1186/s13287-017-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser-modified titanium surfaces enhance the osteogenic differentiation of human mesenchymal stem cells

Abstract: BackgroundTitanium surfaces have been modified by various approaches with the aim of improving the stimulation of osseointegration. Laser beam (Yb-YAG) treatment is a controllable and flexible approach to modifying surfaces. It creates a complex surface topography with micro and nano-scaled patterns, and an oxide layer that can improve the osseointegration of implants, increasing their usefulness as bone implant materials.MethodsLaser beam irradiation at various fluences (132, 210, or 235 J/cm2) was used to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…The final desired outcome of all bone‐implanted biomaterial is the de novo bone formation connecting the implant to the host bone, termed osseointegration, and the majority of the efforts to develop and test new dental implant modifications rely on tests using osteoblasts or MSCs to predict the implant outcome (Bressel et al, 2017; Fu et al., 2009; Jiang et al., 2015; Lotz et al., 2017; Zanicotti et al., 2018). While these types of tests are important to understand the behavior of bone‐forming cells in response to biomaterial modifications, they ignore the contribution of the other cellular and biological processes that occur in the peri‐implant environment in the 14–21 days before bone formation begins that also affect osseointegration and ultimately dictate the fate of the implanted biomaterial (Biguetti et al., 2018; Vlahović et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The final desired outcome of all bone‐implanted biomaterial is the de novo bone formation connecting the implant to the host bone, termed osseointegration, and the majority of the efforts to develop and test new dental implant modifications rely on tests using osteoblasts or MSCs to predict the implant outcome (Bressel et al, 2017; Fu et al., 2009; Jiang et al., 2015; Lotz et al., 2017; Zanicotti et al., 2018). While these types of tests are important to understand the behavior of bone‐forming cells in response to biomaterial modifications, they ignore the contribution of the other cellular and biological processes that occur in the peri‐implant environment in the 14–21 days before bone formation begins that also affect osseointegration and ultimately dictate the fate of the implanted biomaterial (Biguetti et al., 2018; Vlahović et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation of the cell micro-environment using biochemical and biophysical cues is therefore widely explored as a means to alter cell behavior both in vitro and in vivo [ 5 8 ]. Of particular interest are engineered substrates precisely and reproducibly made with defined biophysical properties [ 9 11 ]. Substrates that recapitulate substrate rigidity or surface topographical cues present in the cell environment have been shown in vitro to force cells to behave differently [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laser beam treatment is a controllable and flexible approach to modifying surfaces, which results in surfaces with increased surface area and enhanced wettability, and it displays negligible corrosion and high removal torques of established implants in preclinical bone models[ 64 , 65 ]. Laser-modified titanium surfaces could enhance upregulation of expression of the osteogenic markers and enhance alkaline phosphatase activity of BMSCs[ 66 ]. A recent investigation on the direct metal laser sintering (DMLS) titanium surface found that topographical cues of DMLS surfaces could enhance both protein adsorption ability and BMSC adhesion performance.…”
Section: Surface Topography To Regulate Bone Marrow Mesenchymal Stem mentioning
confidence: 99%